Fat-Soluble Substance Flow During Symbiotic Fungus Cultivation by Leaf-Cutter Ants - Catalani, G. C. [UNESP] (2019)
Leaf-cutter ants perform a series of specialized behaviors in preparing plant substrates for their symbiotic fungus. This process may be related to contamination of workers by substances such as insecticides, leading us to hypothesize that substances are spread among workers through behaviors they perform to grow the fungus. To test this hypothesis, we analyzed the behavioral acts of workers during the processing of the pellets by using a fat-soluble tracing dye, since the active ingredient that composes toxic baits, used for control of leaf-cutter ants, is fat-soluble. The frequencies of performed behaviors were recorded and the number of dyed workers was assessed after fungus cultivation. The most frequent behavior is allogrooming and corresponds to 45.87% of the contamination process in workers, followed by holding, licking, and cutting pellets, which account for 40.22% of the process. After pellet processing, the workers had their external and internal morphological structures marked by the tracing dye-93.75% and 79.25%, respectively. These results confirm that behaviors performed during fungus cultivation contribute to dispersing substances such as insecticides, causing the contamination of workers.